2018
DOI: 10.1002/path.5001
|View full text |Cite
|
Sign up to set email alerts
|

C/ebpα controls osteoclast terminal differentiation, activation, function, and postnatal bone homeostasis through direct regulation of Nfatc1

Abstract: Osteoclast lineage commitment and differentiation have been studied extensively, although the mechanism by which transcription factor(s) control osteoclast terminal differentiation, activation and function remains unclear. CCAAT/enhancer-binding protein α (C/ebpα) has been reported to be a key regulator of osteoclast cell lineage commitment, yet C/ebpα’s roles in osteoclast terminal differentiation, activation and function and bone homeostasis, under physiological or pathological conditions, have not been stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 41 publications
1
22
0
Order By: Relevance
“…While exploring the molecular mechanism(s) underlying the differential regulation of osteoclastogenesis by IL‐20, we found that IL‐20 dose‐dependently upregulated and downregulated the expression of osteoclast‐specific genes and transcriptional activators to perform bone resorption function, such as RANK, CK, TRAP, MT1‐MMP, MMP9, NFATc1 and c‐Fos. In signal transduction, activation of the transcription factors NFATc1 and c‐Fos is mainly regulated by several key signalling pathways including NF‐κB, p38, ERK, JNK and AKT pathways, which are involved in proliferation, apoptosis, differentiation and function in osteoclasts . In this case, NF‐κB, p38 and JNK pathways act as positive regulation in osteoclastogenesis, whereas ERK and AKT pathways are involved in negative regulation .…”
Section: Discussionmentioning
confidence: 99%
“…While exploring the molecular mechanism(s) underlying the differential regulation of osteoclastogenesis by IL‐20, we found that IL‐20 dose‐dependently upregulated and downregulated the expression of osteoclast‐specific genes and transcriptional activators to perform bone resorption function, such as RANK, CK, TRAP, MT1‐MMP, MMP9, NFATc1 and c‐Fos. In signal transduction, activation of the transcription factors NFATc1 and c‐Fos is mainly regulated by several key signalling pathways including NF‐κB, p38, ERK, JNK and AKT pathways, which are involved in proliferation, apoptosis, differentiation and function in osteoclasts . In this case, NF‐κB, p38 and JNK pathways act as positive regulation in osteoclastogenesis, whereas ERK and AKT pathways are involved in negative regulation .…”
Section: Discussionmentioning
confidence: 99%
“…The intracellular osteoclastogenic pathways linked to these stimuli are mediated through distinct RANK-mediated activation of tumor necrosis factor receptor-associated factors (TRAFs) that leads to the feed forward expression and activation of nuclear factor-kappa B (NFκB), c-fos and nuclear factor of activated T cells 1 (NFATc1) in HSCs, ultimately inducing the osteoblast-dependent osteoclast differentiation [40][41][42]. However, several recent studies have addressed the intracellular mechanisms that are interwoven between the adipogenic and osteoclastogenic programs [27][28][29][30][31][32]. In this context, it has been reported that some of the key players known to regulate MSC adipocyte differentiation are expressed and crucial for HSC osteoclast differentiation and likewise, the major osteoclast differentiation factor RANKL is highly expressed in bone marrow adipocytes [27][28][29][30][31][32][33][34][43][44][45][46].…”
Section: Regulation Of Osteoclastogenesis Through the Adipogenic Programmentioning
confidence: 99%
“…Recent studies have revealed that adipogenic transcription factors including PPARγ, C/EBPα and CEBPβ are also expressed and activated in hematopoietic lineage cells during osteoclast differentiation and are critical for the lineage priming, differentiation and activity of osteoclasts [27][28][29][30][31][32][33][34][35]. Furthermore, several adipokines are reported to influence the osteoclastogenic program of HSCs suggesting that increased bone marrow adipogenesis could exert further detrimental effects on bone health by uncoupling osteoblast-osteoclast communication in a fashion that promotes osteoclastogenesis and bone resorption [6,7,[36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…We used 10% sodium dodecyl sulfatepolyacrylamide gel electrophoresis (SDS-PAGE) to perform western blot as described [24,28,29]. MBMs were transfected lentivirus and induced to 5 days for western blot analysis.…”
Section: Western Blot Analysismentioning
confidence: 99%
“…Next, we observed the formation of the F-actin ring, which is an important structure for osteoclast maturation [29]. Equal numbers of MBM cells were seeded on each bone slice and induced by M-CSF and RANKL to generate osteoclasts.…”
Section: F2r Inhibited Osteoclast F-actin Ring Formation On Bone Slidesmentioning
confidence: 99%